Investigation of DNA methylation at the promoter region of the aralkylamine N-acetyltransferase (AANAT ) gene in South African children with Autism Spectrum Disorder - Van Wyk, Gerrit (Department of Molecular and Cell Biology, 2018)
Sleep problems and suppressed melatonin production commonly presents with core Autism Spectrum Disorder (ASD) traits. Aralkylamine N-acetyltransferase (AANAT) acts as the penultimate and rate-limiting enzyme in the melatonin biosynthetic pathway, and a study by Hu et al. (2009) reported that AANAT expression was suppressed in an ASD population with severe language impairments. The mechanism responsible for this suppressed expression is unknown. Therefore, the aim of the study was to investigate the genetic and epigenetic features of AANAT in a cohort of South African children with ASD versus children with typical development in combination with a melatonin production study to explore melatonin's contribution to ASD symptomatology. It was expected that meeting this aim would reveal DNA methylation (DNAme) modifications were statistically significant different between case and control participants. Alternatively, that DNAme features would correlate with distinct ASD traits or sleep problems and/or altered melatonin production in case participants. Biological samples and phenotypic data were collected from boys, aged between 6 and 14 years old who were assessed with the Autism Diagnostic Observation Schedule (ADOS-2). The promoter region and gene body of AANAT was sequenced (case n=26, control n=26) and DNAme analysis was performed with the Epityper massARRAY system (case n=19, control n=20). Urinary 6-hydroxymelatonin sulphate (6-OHMS) was quantified with an enzyme-linked immunosorbent assay (case n=4, control n=4). The 6-OHMS investigation was complemented with actigraphy data and a description of sleep behaviour as determined by an abbreviated version of the Children's Sleep Questionnaire. Sequence analysis found no novel single nucleotide polymorphisms and no significant differences between case and control participants. In contrast, a difference (p=0.014) in DNAme at the third CpG site in the promoter region (CpG 3) was identified in case participants assessed with ADOS-2 Module 1 in comparison to case participants assessed with ADOS-2 Modules 2 - and 3. In particular, hypomethylation was more common in participants assessed with Module 1 which is the module used to assess participants with little or no speech abilities. The transcription factor (TF) binding motifs for ZID (zinc finger protein with interaction domain), MEIS1 (Meis homeobox 1) and ZIC1 (zinc finger protein of the cerebellum 1) were identified at or near to CpG 3. These three TFs have known gene ontology terms that relate to neurodevelopment. The age of participants did not correlate with DNAme, and no further statistical significant differences were identified between the DNAme features of case and control participants, nor the correlation analysis of DNAme and ASD traits in case participants. No Module 1 participants volunteered for the 6-OHMS study, and it was therefore not possible to confirm whether DNAme features at CpG 3 correlated with altered melatonin production. The data from the study suggest that hypomethylation at the promoter region of AANAT may be related to speech impairment in ASD, and that epigenetic investigations can uncover molecular underpinnings that correlate to ASD symptomatology. Furthermore, the current study addresses the paucity of molecular information on ASD in Sub-Saharan Africa and thereby contributes to a comprehensive understanding of disease biology. It remains unknown if hypomethylation at AANAT also correlates with suppressed melatonin synthesis in ASD individuals with speech impairments and this need further investigation.